PENGARUH KEPEMIMPINAN DAN KOMUNI PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA BALAI PENGELOLA TRANSPORTASI DARAT KELAS II SUMATERA BARAT: PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA BALAI PENGELOLA TRANSPORTASI DARAT KELAS II SUMATERA BARAT - Sumarta Endra; Zefriyenni; Lusiana (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
This research aims to determine the influence of leadership and communication on employee performance through work motivation as an intervening variable at Balai Pengelola Transportasi Darat Kelas II Sumatera Barat. The method used was multiple linear regression analysis and path analysis, by distributing a questionnaire to 51 respondents to Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees, 51 respondents returned the questionnaire. The results obtained show that there is a positive and significant influence of leadership on work motivation of Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees. There is a positive and insignificant effect of communication on work motivation of Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees. There is a positive and significant influence of leadership on employee performance for Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees. There is a positive and insignificant effect of communication on employee performance for Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees. There is a positive and significant influence of work motivation on employee performance among Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees. Work motivation is able to mediate the influence of leadership on employee performance for Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees. Work motivation has not been able to mediate the influence of communication on employee performance for Balai Pengelola Transportasi Darat Kelas II Sumatera Barat employees. Finally, the author suggests to Balai Pengelola Transportasi Darat Kelas II Sumatera Barat to further improve leadership because it has the most dominant influence on employee performance so it is hoped that employee performance can increase. Keywords: Leadership, Communication, Work Motivation and Employee Performance